Muscle Tonicity of Children with Spastic Cerebral Palsy: How Effective Is Swedish Massage? - Alizad, V.; Sajedi, F.; Vameghi, R. (Iranian Journal of Child Neurology, 2009)
Objective Massage therapy is one of the most widely used complementary and alternative medicine therapies for children. This study was conducted to determine the effect of Swedish massage on the muscle tonicity of children with spastic cerebral palsy (CP). Materials & Methods This study was a single blind clinical trial conducted on forty children with spastic CP, recruited from clinics of the University of Social Welfare & Rehabilitation Sciences. They were randomly assigned to intervention and control groups. Routine occupational therapy techniques were performed during a 3 monthperiod in both groups, while the intervention group also received Swedish massage for 30 minutes before every rehabilitation session. Muscle tonicity was evaluated at the beginning of the study and 3 months later using the Modified Ashworth Scale. Results The average ages of children in the intervention (n=13) and control (n=14) groups were 49.5 and 42.1 months respectively. Although after intervention, tonicity of upper and lower limbs, trunk and neck in the intervention group in comparison with controls had no significant differences, there were statistically significant differences in reduction rate of tonicity in upper limbs and trunk between the two groups (P <0.05). Conclusion Massage therapy is not a panacea for improvement of spasticity in children with CP but the encouraging results of other studies on children with CP indicate that further studies are needed for more definite results.